Intramolecular Hydrogen Bonding and Tautomerism in Schiff Bases: Synthesis, Spectroscopic and Theoretical Studies of N-(2,2'-Methylenebis(4-methoxyphenyl)salicylidene and N-(2,2'-Methylenebis(4-methoxyphenyl)-2-oxonaphthalidene-methylamine - Dal, Hakan (Asian Journal of Chemistry, 2014)
The new Schiff bases (4 and 5) were synthesized respectively from the reaction of 2,2'-methylenebis(4-aminomethoxybenzene) (3) with salicylaldehyde and 2-hydroxy-1-naphthaldehyde. The products have been characterized by elemental analysis, FTIR, UV-visible and NMR techniques. The tautomeric equilibria of 2-hydroxy Schiff bases were investigated in polar, non-polar, acidic and basic media by using UV-visible absorption spectra. Compound 4 is in, predominantly, phenol-imine (O-H···N) form, whereas compound (5) is in tautomeric equilibria (phenol-imine, O-H···N and keto-amine, O···H-N forms) in polar and non-polar solvents, as supported by 1H NMR and UV-visible data. All of the NMR assignments were made using 1H, 13C NMR and aided by 2D COSY, NOESY, HETCOR and HMBC heteronuclear correlation techniques. In addititon, theoretical calculations have been carried out PM6 methods in the MOPAC2009 and Marvinbeans-5_3_01-windows programs. The heat of formation (DHf), enthalpy (DH), entropy (DS) Gibbs free energy (DG), conformations and tautomers of the synthesized compounds are estimated by using MOPAC2009 (PM6) program.